2014
DOI: 10.1038/labinvest.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 signaling activates bone marrow-derived fibroblasts in renal fibrosis

Abstract: Recent studies have demonstrated that bone marrow-derived fibroblasts contribute significantly to the pathogenesis of renal fibrosis. However, the signaling mechanisms underlying the activation of bone marrow-derived fibroblasts in the kidney are incompletely understood. Since TGF-β1/Smad3 signaling has been shown to play an important role in the pathogenesis of kidney fibrosis, we investigated the role of Smad3 in the activation of bone marrow-derived fibroblasts in the kidney following obstructive injury usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…[6][7][8][9]17,20,21 Recruitment of these circulating fibroblast precursors depends on locally produced chemokines. We previously showed that chemokine CXCL16 and its receptor CXCR6 play a critical role in recruiting these cells from the circulation to the injured kidney after obstructive injury, ischemia-reperfusion, and angiotensin II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8][9]17,20,21 Recruitment of these circulating fibroblast precursors depends on locally produced chemokines. We previously showed that chemokine CXCL16 and its receptor CXCR6 play a critical role in recruiting these cells from the circulation to the injured kidney after obstructive injury, ischemia-reperfusion, and angiotensin II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,10,11 The activation of myeloid fibroblast precursors is regulated by locally produced cytokines. 7,8,17 Profibrotic cytokines IL-4 and IL-13 promote fibrocyte differentiation, whereas antifibrotic cytokines IFN-g and IL-12 inhibit its differentiation, suggesting that a complex interplay in the inflamed milieu determines the fate of bone marrow-derived fibroblast precursors. 14,15 Naive CD4 + T cells can differentiate into two major distinct phenotypes, Th1 and Th2 cells, which are characterized by specific cytokine expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 A recent study has revealed that the TGF-b1-Smad3 pathway induces the transition of monocytes to bone marrow-derived fibroblasts in the course of renal fibrosis. 20 Yan et al 17 showed in this study that TGF-b1-induced expression of aSMA, fibronectin, and COLI was not affected by the pretreatment with CP690550 in rat kidney fibroblasts. These results indicate that the effect of CP690550 on the transition of monocytes to bone marrow-derived fibroblasts could be independent of the TGF-b1-Smad3 pathway; however, an experiment using TGF-b1-treated bone marrow-derived monocytes and CP690550 will be required to clarify it.…”
mentioning
confidence: 47%